Implementation of Interpersonal Communication to The Broken Home Family in Psychological Rescue Effort - Muhammad Nur Fadli Nasution; Muhammad Alfikri (PT Mattawang Mediatama Solution, 2022)
The purpose of this study is to determine how interpersonal communication is important in broken home families so that children do not develop psychological disorders or violate norms. Broken families are a social phenomenon that should not occur but has become common in Indonesia. This study employs a qualitative descriptive method, with data collected through interviews, observations, and documentation. According to the findings, eight factors contributed to a broken home: 1) communication disorders, 2) egocentricity, 3) dissatisfaction, 4) economy, 5) time, 6) lack of education, 7) third party disturbances, and 8) disturbances. psychological. Parents play an important role in establishing interpersonal communication so that no more children engage in harmful behaviors that violate norms. Furthermore, parents implemented a number of interpersonal communication strategies in order to establish an intimate and intimate relationship with their children.